2022
DOI: 10.3389/fphar.2022.1009550
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the therapeutic application and pharmacological properties of kinsenoside against inflammation and oxidative stress-induced disorders

Abstract: Extensive research has implicated inflammation and oxidative stress in the development of multiple diseases, such as diabetes, hepatitis, and arthritis. Kinsenoside (KD), a bioactive glycoside component extracted from the medicinal plant Anoectochilus roxburghii, has been shown to exhibit potent anti-inflammatory and anti-oxidative abilities. In this review, we summarize multiple effects of KD, including hepatoprotection, pro-osteogenesis, anti-hyperglycemia, vascular protection, immune regulation, vision prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 152 publications
0
3
0
Order By: Relevance
“…Alcohol-induced changes in iron metabolism have also been implicated in ALD. Alcohol is believed to upregulate iron absorption by downregulating expression of hepcidin 53,54 The resultant iron overload contributes to ethanol induced oxidative stress by activating Kupffer and hepatic stellate cells, and triggering ferroptosis, a programmed iron-dependent cell death. 53…”
Section: Pathophysiology Of Aldmentioning
confidence: 99%
“…Alcohol-induced changes in iron metabolism have also been implicated in ALD. Alcohol is believed to upregulate iron absorption by downregulating expression of hepcidin 53,54 The resultant iron overload contributes to ethanol induced oxidative stress by activating Kupffer and hepatic stellate cells, and triggering ferroptosis, a programmed iron-dependent cell death. 53…”
Section: Pathophysiology Of Aldmentioning
confidence: 99%
“…Kinsenoside is one of the major active compounds in Anoectochilus sp. [43] and exerts antioxidant, anti-hyperglycemia, anti-inflammation abilities [44,45]. Moreover, our previous study reported that the kinsenoside found in A. burmannicus exhibits anti-inflammation and anti-obesity activities [31,42].…”
Section: Characterization Of a Burmannicus Ethanolic-extract-synthesi...mentioning
confidence: 99%
“…The body regularly produces ROS in minute portions, which are essential elements responsible for the regulation of a series of processes, including the preservation of cell homeostasis and operations such as signal transduction, gene function, and receptor activation (Ho et al, 2022). Numerous studies have implied that oxidative stress and inflammation are the two processes that frequently co‐exist in an inflammatory environment (Lu et al, 2022). At the region of inflammation, inflammatory cells emit a number of ROS, giving rise to exaggerated oxidative damage (Du et al, 2022; Gupta et al, 2022).…”
Section: Introductionmentioning
confidence: 99%